(untitled) - Sandy Cairncross (Chichester, New York, 1993)
This book is concerned with policy nad trategies for implementing water and sanitation programmes. This book contains a distillation of much knowledge and experience and many people have contributed to it in various ways
Keywords: sanitary engineering - developing countries,sanitary engineering - tropical conditions